The Impact of Corporate Governance, Leverage, and Profitability on Intellectual Capital Disclosure with Company Size as a Moderating Variable - Mellany Koernia; Ari Dewi Cahyati (JAFFA, 2022)
This research focuses to examine the impact of Corporate Governance, Leverage, and Profitability on Intellectual Capital Disclosure with Company Size as a Moderating Variable. This research method is descriptive method with a quantitative approach. The data used in this study is secondary data, namely the annual report obtained from www.IDX.co.id and the corporate governance perception index report obtained from The Indonesian Institute for Corporate Governance. The number of samples is 46 data with the technique of taking using the purposive sampling method. The findings of this study demonstrate that the Corporate Governance variable has no impact on Intellectual Capital Disclosure, Leverage and Profitability variables have a negative and significant impact on Intellectual Capital Disclosure, the company Size variable cannot moderate the relationship linking Corporate Governance and Intellectual Capital Disclosure, and the company Size variable can strengthen the relationship linking Leverage and Profitability on Intellectual Capital Disclosure. This study can be implemented by corporates to analyze the role of corporate governance, leverage, and profitability on intellectual capital disclosure with company size as a moderating variable and is expected to be a reference in policy making by corporates management to increase its intellectual capital.disclosure.